Demand-side constraints and structural adjustment in Sub-Saharan African countries - Koester, Ulrich; Schafer, Hartwig; Valdes, Alberto (International Food Policy Research Institute, 1990)
Structural adjustment policies are recommended and financially supported by the World Bank and the International Monetary Fund as part of an effort to solve the external account crisis prevailing in many developing countries, including some African countries. Structural adjustment programs include policy reforms implemented in various sectors and pursue, almost without exception, outward-oriented trade strategies. One aspect of structural adjustment programs is the potential for expanded product ion of agricultural tradables in SubSaharan Africa. Much of this expansion is expected to increase the volume of agricultural exports. Although the expanded production of importables, particularly food, could be significant, the situation in African countries deserves particular attention because their production is highly concentrated on a few export commodities. If most African countries promoted and expanded their exports at the same time, world prices would. decrease. Is there a risk that, at least in the short or medium term, the structural adjustment programs could worsen the economic situation in Sub-Saharan Africa? If so, this demand-side constraint could counteract one objective of the recommended structural adjustment policy.